DETERMINATION OF RESIDUAL SOLVENTS IN PSMA 11 - AN ACTIVE PHARMACEUTICAL SUBSTANCE IN PSMA-11 KIT FOR Ga-68 LABELLING - Robert Lipka; Agnieszka Kokoszka; Agnieszka Sawicka (Polskie Towarzystwo Farmaceutyczne, 2023)
A selective, sensitive and low sample consumption GC method for determination of residual solvents in PSMA samples was developed. Selectivity with respect to solvents such as ethanol, diethyl ether, 2-propanole, acetonitrile, dichloromethane, used in manufacturing of PSMA-11, was obtained on two different GC systems and columns. In all these cases, good separation and other system suitability parameters were obtained. The values of detection limit (LOD) and limit of quantitation (LOQ) were estimated and verified experimentally for ethanol, diethyl ether, 2-propanol (IPA), acetonitrile (ACN) and dichloromethane. Full validation parameters i.e.: selectivity, limit of detection (LOD), limit of quantitation (LOQ), linearity, precision, accuracy, robustness and system suitability parameters are presented with respect to ACN and IPA. Accuracy and precision were measured on two GC systems. Statistical tests exhibit, that there are no significant differences in accuracy and precision between two GC systems